A low resistivity n++-InGaN/p++-GaN polarization-induced tunnel junction. (11th February 2016) - Hu, Weiwei; Zhang, Shuming; Ikeda, Masao; Chen, Yigang; Liu, Jianping; Feng, Meixin; Li, Deyao; Zhang, Feng; Zhou, Kun; Tian, Aiqin; Yang, Hui
Abstract: A low resistivity n ++ -InGaN/p ++ -GaN tunnel junction is illustrated. The tunneling current density of tunnel junction with 30 percent In content in InGaN layer turns out to be extraordinary high (10 kA cm −2 ) even at a relatively low bias voltage (0.1 V) compared with traditional n ++ -GaN/p ++ -GaN. And we optimize the InGaN layer including the thickness, indium component and the doping concentration to increase the tunneling probability with the 1D Schrödinger Poisson self-consistent method and WKB (Wentzel-Kramers-Brillouin) approximation. It is shown that the peak value of electric field in tunnel junction caused by spontaneous polarization and piezoelectric effect reaches 7.1 MV cm −1 with the 2D hole gas concentration of 2  ×  10 20 cm −3 at the interface between InGaN and GaN. That indicates n ++ -InGaN/p ++ -GaN tunnel junction has a potential application in GaN-based optoelectronic device.